Human Resource Practices and Employee Turnover Intentions: Do Organizational Commitment Mediates and Social Support Moderates the Relationship? - Asad, Muzaffar (International Journal of Psychosocial Rehabilitation, 2020)
Banking sector is considered as backbone of any economy. The triumph of any business depends on its employees and banking sector has no exception to it. Every business organization develop rules to retain their loyal and hardworking employees, yet businesses all over the world face the issue of employee turnover, which is a consequence of employee turnover intentions. In Pakistan banking sector is among those industries where employee turnover is very high and employee switching is a big challenge for the banks. Employees with turnover intentions do not only cause the issue of employee turnover but their performance is also low as compared to loyal employees. One of the several reasons behind employee turnover intentions are human resource practices which helps in the development of organizational commitment among employees. Social support, if received, is a major hurdle in development of employee turnover intentions. In the literature, it has been observed that research over the issue of employee turnover intentions has explicitly focused on human resource practices. However, role of human resource practices in developing organizational commitment and its influence over the employee turnover intentions has not gained much attention. Similarly, the role of social support has also not been catered simultaneously with organizational commitment. Thus, the purpose of this study is to identify the mediating role of organizational commitment and moderating role of social support between human resource practices and employee turnover intentions. The findings of the study enrich social exchange theory by adding the mediating role of organizational commitment and moderating role of social support. The results support the entire framework developed in the study.